Professional work : knowledge, power and social inequalities - Gorman, Elizabeth M.; Vallas, Steven P. 1951- (Emerald Publishing Limited, 2020)
The professions have undergone massive changes in recent decades, as globalization, information technology, bureaucratization and market competition have begun to envelop even the most prestigious occupations in contemporary societies. Ironically, at a time when expert knowledge has grown increasingly important, the 'golden age' of the professions has receded into the past. Professional autonomy, authority, and ethics are all under siege, and even their claims to exclusive control of knowledge face challenges on multiple fronts. Volume 34 of Research in the Sociology of Work explores how the professions are faring in this changed world, shedding new light on a field that has long been at the center of social science thinking about the economy, the state, and social order. Chapters in this volume explore a series of questions that are vital to modern life, such as: How has increased control by employers and clients altered the experience of work for professionals? What are the new bases of professional status? How are underrepresented groups faring within the professions? How do professionals respond to precarity and unemployment?- Resumé vydavatel
Includes index.
Keywords: profese -- sociologické aspekty; professions -- sociological aspects; elektronické knihy; sborníky; electronic books; papers of several authors